Urgensi Kemampuan Komunikasi Interpersonal Bagi Pustakawan - Ema Puji Lestari (IAIN Ponorogo, 2015)
To serve, librarian will meet users of many characters and behaviours. If librarians have and able to implement skill of interpersonal communication, it will bear a positive impression from users, he can treat one person with specifc treatment, and other person with other treatment, so every users will be satisfed. This article dealts with how to increase interpersonal communication skill of librarians, so that they can undergo their activities smoothly.